Integrating primary care of chronic respiratory disease, cardiovascular disease and diabetes in Brazil: Practical Approach to Care Kit (PACK Brazil): study protocol for randomised controlled trials - Bachmann, Max O.; Bateman, Eric D.; Stelmach, Rafael; Cruz, Álvaro A.; de Andrade, Matheus Pacheco; Zonta, Ronaldo; Zepeda, Jorge; Natal, Sonia; Cornick, Ruth; Wattrus, Camilla; Anderson, Lauren; Lombard, Carl; et al. (Journal of Thoracic Disease; Vol 10, No 7 (July 31, 2018): Journal of Thoracic Disease, 2018)
Background: Multimorbidity is increasing common in Brazilian adults. Comorbid chronic lung disease, cardiovascular disease and diabetes are often inaccurately diagnosed or ineffectively treated. The Global Alliance against Chronic Respiratory Diseases (GARD) aims to strengthen health systems to prevent and control non-communicable diseases through primary health care. The Practical Approach to Care Kit (PACK Adult) is a clinical decision support tool that provides evidence-supported algorithmic guidelines for screening, diagnosis and treatment of chronic diseases, and is widely used in South Africa. It was adapted for Brazil by family physicians in the Florianopolis City Health Department, which trains clinic doctors and nurses to use it. Methods: Effectiveness of PACK Adult training will be evaluated in two pragmatic cluster randomised trials, one enrolling adults with chronic lower respiratory diseases and the other enrolling adults with cardiovascular disease or diabetes. Forty-eight municipal clinics in Florianopolis were randomly allocated to intervention or control arms. In intervention arm clinics, doctors and nurses will receive educational outreach training and the PACK Adult clinical decision support tool. In control arm clinics, doctors and nurses will receive only the tool. Trial outcomes will be measured using patients’ electronic medical records during 12 months after completion of basic training. Primary outcomes for the respiratory trial are appropriate prescribing, spirometry and diagnosis rates. Primary outcomes for the cardiovascular trial are testing for cardiovascular risk and diabetes, and systolic blood pressure. Educational outreach to primary care professionals could improve respiratory, cardiovascular and diabetes care in Brazil. Trial registration: NCT02786030 and NCT02795910 (https://clinicaltrials.gov/)